ANALISIS BEBAN KERJA OPERATOR DI BAGIAN PRODUKSI DENGAN METODE CARDIOVASCULAR LOAD (CVL) DAN BOURDON WIERSMA UNTUK MENGURANGI KELELAHAN DI CV. XYZ - Enny Aryanny; Bayyinah Baitil (Tekmapro : Journal of Industrial Engineering and Management, 2021)
The workforce of plastic crushing and product printing at CV. XYZ experiences fatigue most quickly, so when working often makes mistakes and lacks concentration at work which causes a decrease in work output. The workload on the operator of the plastic crushing section has oxygen consumption of 0.953 liters / minute categorized by Weight, with a Cardiovascular Load percentage of 30.54% categorized as required for improvement based on the results of Bourdon Wiersma 10.4 seconds speed level category Good Enough, accuracy level 12.7 Doubtful category, a constant level of 5.7 seconds Fair category. The operator of the product printing section has an oxygen consumption of 1,083 liters / minute categorized by Weight, with a percentage of Cardiovascular Load of 35.71% categorized as needed an improvement based on the results of the Bourdon Wiersma speed level of 10.9 seconds the category Good Enough, the level of accuracy 17.6 Doubts category - Doubt, a constant level of 7.01 seconds in the Doubt-free category. Improvements that can be made to plastic crushing and product printing operators are adding rest periods, rolling workers' systems, improving workplace conditions to be more ergonomic, and managing work shifts.. Keywords: Oxygen Consumption, Accuracy, Speed, Constant.